TRANSFORMASI BUDAYA ORGANISASI ISLAMI DALAM MEMBANGUN LINGKUNGAN BELAJAR BERORIENTASI MUTU DI MADRASAH - M. Holili (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to describe about the transformation of Islamic organizational culture in madrasah as a strategic effort to develop a quality-oriented learning environment. Using a literature review approach, that examine the role of spirituality, leadership, and management innovation in enhancing educational quality within Islamic institutions. The results reveal that Islamic organizational culture anchored in values such as sincerity (ikhlas), trustworthiness (amanah), and collective responsibility serves as a moral and managerial foundation for creating effective and sustainable educational systems. Furthermore, spiritual leadership emerges as a key driver in strengthening teachers' professional commitment and fostering continuous quality improvement. Madrasah that successfully integrate Islamic values into their management practices demonstrate higher levels of teacher satisfaction, student engagement, and institutional effectiveness. However, challenges remain in bridging the gap between ideal Islamic values and real-world administrative practices, particularly in resource-limited institutions. The study concludes that the transformation of Islamic organizational culture must be positioned as a central agenda in the quality development of madrasah. By harmonizing spiritual values with modern quality management principles, Islamic educational institutions can not only improve academic performance but also cultivate ethical and holistic human resources